(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
History proves that the Kyrgyz have repeatedly created their own state in the struggle for freedom and independence for many centuries. As part of the Huns, in the present century, the Enesai Kyrgyz Khaganate, the Great Kyrgyz Power, the efforts of our medieval ancestors for independence, as well as the formation of statehood during the Soviet era, provide information about the consistent, unceasing struggle of our ancestors for statehood. Such fighters for the independence of Kyrgyzstan as Barsbek, Mohammed Kyrgyz, Erenek, Kubat and Tagai, in Soviet times - Imanaly Aidarbekov, Zhusup Abrakhmanov, Abdikadir Orozbekov, Bayaly Isakeev and others who devoted their lives to the struggle for freedom of the Kyrgyz people, for a free state are clear evidence.